Dimensi Hidup Berkenan Kepada Allah Menurut Roma 12:1-8 Dan Etika Bertanggung Jawab - Rudy Budiatmaja; Seno Lamsir; Rikardo Sianipar (Vox Dei: Jurnal Teologi dan Pastoral, 2023)
The purpose of living a life pleasing to God means that every believer must meet God's standards, not all humans can fulfill them because of human sinfulness itself. As a result of sins committed from all human actions, in order to live to please God, all counselors and counselees must meet God's standards, but the problem is that the counselee's life is found by the counselor himself, still in acts of the flesh that do not show the standard of God's approval. This research article uses content analysis and qualitative data as literature research. Counselees who have problems in social life such as tattooing their bodies, often smoking, live rah-rah tend to get drunk making their future full of failures. The current research shows the results that state that the dimensions of life pleasing to God must be obeyed by every counselor and counselee as believers and practice it in various activities in daily life so that each counselee can live willingly, namely meeting God's standards. The novelty in this study uses ethical theory to be responsible for each counselee to act in the dimension of life pleasing to God. The conclusion is that every counselor and counselee as a believer must live a holy life, be faithful in worship, use the gifts that God has given well to contribute to the benefit of many people, behave well and please God.